Insertion sequence-mediated phage resistance contributes to attenuated colonization of cytolytic Enterococcus faecalis variants in the gut - Jumpei Fujiki; Tomohiro Nakamura; Henriette Kreimeyer; Cristina Llorente; Derrick E. Fouts; Bernd Schnabl (Microbiology Spectrum)
ABSTRACT Specific elimination of cytolytic Enterococcus faecalis from the intestinal microbiota by bacteriophages (phages) attenuates ethanol-induced liver disease in pre-clinical studies; however, other clinical phage therapy studies have reported the occurrence of phage-resistant variants. Here, we assessed phage resistance using a cytolytic E. faecalis clinical isolate, EF01. After infecting EF01 with ΦEf2.1 (Myoviridae) or ΦEf2.2 (Podoviridae), four host variants (R-EF01ΦEf2.1-A and R-EF01ΦEf2.1-B from infection with ΦEf2.1, and R-EF01ΦEf2.2-A and R-EF01ΦEf2.2-B from infection with ΦEf2.2) were isolated. Although isolate R-EF01ΦEf2.2 exhibited resistance to both phages, isolate R-EF01ΦEf2.1 demonstrated partial resistance only to ΦEf2.1. Whole-genome sequencing of these four isolates revealed an insertion sequence, IS256, -mediated disruption of xylA in R-EF01ΦEf2.1-A and R-EF01ΦEf2.1-B. In addition, a non-synonymous mutation in epaR, essential for the complete Enterococcus polysaccharide antigen (Epa), was identified in the R-EF01ΦEf2.2-A isolate. Furthermore, R-EF01ΦEf2.2 isolates exhibited IS256-associated chromosomal deletions and lacked galE, a gene involved in Epa biosynthesis. After gavaging mice with EF01 WT, R-EF01ΦEf2.1-A, R-EF01ΦEf2.2-A, and R-EF01ΦEf2.2-B isolates, colonization of R-EF01ΦEf2.2 isolates was significantly attenuated. R-EF01ΦEf2.2 isolates exhibited less resistance to the bile salt sodium deoxycholate and showed reduced adherence to intestinal cell monolayers, suggesting that phage-resistant variants with alterations in bacterial surface molecules, potentially including those involved in Epa biosynthesis, reduced pathogen fitness by attenuating gut colonization. In summary, IS256 is involved in phage resistance of a cytolytic E. faecalis clinical isolate, and certain phage resistance mechanisms could contribute to favorable clinical outcomes by promoting the swift elimination of phage-resistant variants in the treatment of alcohol-associated hepatitis.IMPORTANCEPhage therapy is a promising approach for precise editing of the gut microbiota. Notably, the specific elimination of cytolytic E. faecalis from the intestinal microbiota by phages attenuates ethanol-induced liver disease in pre-clinical studies. Despite the great promise of phage therapy, the occurrence of phage-resistant variants represents a concern for the successful development of phage-based therapies. In this context, we assessed phage resistance using a cytolytic E. faecalis clinical isolate. Isolated phage-resistant variants acquired mutations or deletions of Epa biosynthesis-related genes and exhibited attenuated colonization in the gut. These phage-resistant variants showed less resistance to bile salts and reduced adherence to intestinal cell monolayers. These results suggest that even if phage-resistant variants arise during phage therapy, certain mechanisms of phage resistance may contribute to the rapid elimination of phage-resistant variants promoting favorable clinical outcomes in the treatment of alcohol-associated hepatitis.